Oral health related knowledge, attitude and practice among nursing students of Kathmandu – a pilot study - Bhattarai, Rosina; Khanal, Sunita; Rao, G Nagaraja; Shrestha, Sujita (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The objective of the study was to assess the oral health related knowledge, attitude and practices of bachelors level nursing college students in Kathmandu district. Materials & Methods: Data was collected using pre-designed questionnaire among 251 nursing students of three colleges comprising of 43 closed ended questions adopted from various studies. Twenty five questions related to knowledge, 8 questions of attitude and 10 of practice were asked. Prior to conducting the study permission was obtained from institutional review board of Kantipur Dental College and from the Campus Chief of the nursing colleges. Results: Majority of respondents had good oral health knowledge including functions of teeth (94.0%), mineral important for tooth formation (98.4%), vitamin necessary for growth and development of teeth (91.2%), dental caries (90.4%), gingival diseases (96.4%) and treatment for malocclusion (90.8%). Almost half of the participants did not know about treatment options for gum disease, consequences of irregular teeth and causes of oral cancer. Majority of the participants showed good attitudes towards oral health with 99.2% giving equal importance to their teeth like their general health. 78.9% of the participants brush twice daily with 98% using toothbrush and toothpaste among whom 65.7% uses soft bristle toothbrushes. Conclusion: It was seen that oral health related knowledge, attitude and practice of nursing students was adequate but further improvements can be encouraged and facilitated.